Benzyl Alcohol Assisted Synthesis and Characterization of Highly Reduced Graphene Oxide (HRG)@ZrO2 Nanocomposites. Issue 10 (7th April 2017) - Shaik, Mohammed R.; Al‐Marri, Abdulhadi H.; Adil, Syed F.; Mohri, Nils; Barton, Bastian; Siddiqui, Mohammed R. H.; Al‐Warthan, Abdulrahman; Labis, Joselito P.; Tremel, Wolfgang; Khan, Mujeeb; Tahir, Muhammad N.
Abstract: We demonstrate a one‐step solvothermal synthesis of HRG@ZrO2 nanocomposites using benzyl alcohol as solvent and stabilizing ligand. The as‐synthesized HRG@ZrO2 hybrid nanocomposites showed a homogeneous distribution of the ZrO2 NPs (≈ 5 nm) onto HRG nanosheets. High resolution (HR)TEM, X‐ray diffraction (XRD), and Raman spectroscopy confirmed the presence of cubic ZrO2 . The presence of benzyl alcohol as stabilizing ligand was demonstrated by ultraviolet‐visible (UV‐vis), Fourier‐transform infrared (FT‐IR) spectroscopy and thermogravimetric analysis (TGA). The reduction of graphene oxide to HRG was also realized by X‐ray photoelectron spectroscopy (XPS). A study of the HRG@ZrO2 formation mechanism revealed that benzyl alcohol adsorbs on HRG through π‐π interactions between the planar benzene ring of benzyl alcohol and the HRG nanosheets. The hydroxyl groups act as anchor groups to facilitate the nucleation of ZrO2 NPs. The effect of the metal oxide precursor concentration on the coating density of ZrO2 NPs was studied by preparing HRG@ZrO2 nanocomposites with different concentrations of zirconium precursor. Abstract : Solvothermal synthesis for the highly reduced graphene oxide (HRG) coated with ZrO2 nanoparticles using benzyl alcohol as solvent and stabilizing ligand is presented. The planar benzene ring of benzyl alcohol facilitates non‐covalent functionalization of graphene sheets, rendering it rich with OH groups to nucleate ZrO2 . Since benzyl alcohol route for the synthesis of metal oxides is well established, the protocol can be easily extended for the synthesis of other graphene‐metal oxide nanocomposites.